Long-term persistence of high anti-PF4 antibodies titer in a challenging case of AZD1222 vaccine-induced thrombotic thrombocytopenia - Luca Barcella; Chiara Ambaglio; Paolo Gritti; Francesca Schieppati; Varusca Brusegan; Eleonora Sanga; Marina Marchetti; Luca Lorini; Anna Falanga (Bleeding, Thrombosis and Vascular Biology, 2023)
A syndrome occurring after adenoviral vector anti-SARS-CoV-2 vaccination, characterized by thrombocytopenia, venous thrombosis, and circulating anti-PF4 antibodies, known as vaccine-induced immune thrombotic thrombocytopenia (VITT), is well described. Data on the long-term course of this syndrome are lacking. Our aim is to report the clinical and laboratory features of a patient with VITT from diagnosis and during 21 months of follow-up. Cerebral venous thrombosis associated with elevated D-dimer, low fibrinogen, thrombocytopenia, and anti-PF4 antibodies positivity occurred in this patient after ChAdOx1 nCoV-19 vaccination. Cerebral thrombosis required a revascularization procedure and decompressive craniectomy. Upon dexamethasone and anticoagulant treatment initiation, the platelet count recovered. However, a persistently high anti-PF4 antibody titer, without thrombosis recurrence, was observed. Little is known about the long-term persistence of anti-PF4 antibodies, their clinical significance, and their possible role in guiding therapeutic decisions. In our patient, we decided to continue anticoagulant treatment beyond 21 months with parallel anti-PF4 antibody monitoring.